2018
DOI: 10.3748/wjg.v24.i34.3813
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of microbiome in patients with decompensated cirrhosis

Abstract: Cirrhosis is an increasing cause of morbidity and mortality. Recent studies are trying to clarify the role of microbiome in clinical exacerbation of patients with decompensated cirrhosis. Nowadays, it is accepted that patients with cirrhosis have altered salivary and enteric microbiome, characterized by the presence of dysbiosis. This altered microbiome along with small bowel bacterial overgrowth, through translocation across the gut, is associated with the development of decompensating complications. Studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…It has been shown that microbiota of the sigmoid colon in liver cirrhosis patients differs in those with HE when compared with patients without HE [51]. Gut dysbiosis in liver cirrhosis also contributes to the development of Spontaneous Bacterial Peritonitis (SBP) through damaged intestinal barrier and a higher degree of microbial translocation [52].…”
Section: Disbyosis and Liver Diseasesmentioning
confidence: 99%
“…It has been shown that microbiota of the sigmoid colon in liver cirrhosis patients differs in those with HE when compared with patients without HE [51]. Gut dysbiosis in liver cirrhosis also contributes to the development of Spontaneous Bacterial Peritonitis (SBP) through damaged intestinal barrier and a higher degree of microbial translocation [52].…”
Section: Disbyosis and Liver Diseasesmentioning
confidence: 99%
“…Prolonged liver inflammation results in cirrhosis and end-stage liver disease (ESLD) that places patients at risk for spontaneous bacterial peritonitis (SBP), hepatic encephalopathy (HE), and ultimately hepatocellular carcinoma (HCC). 139 Compared with healthy individuals, patients with cirrhosis have slower intestinal transit time, intestinal bacterial overgrowth, and altered fecal microbial profiles, with enrichment of Proteobacteria and Fusobacteria and reduced Bacteroidetes. [139][140][141][142] Fecal microbial signatures of patients with cirrhosis vary with disease severity (compensated vs uncompensated cirrhosis) and might be used to predict outcomes of hospitalized patients.…”
Section: Cirrhosis Spontaneous Bacterial Peritonitis Hepatic Encephmentioning
confidence: 99%
“…139 Compared with healthy individuals, patients with cirrhosis have slower intestinal transit time, intestinal bacterial overgrowth, and altered fecal microbial profiles, with enrichment of Proteobacteria and Fusobacteria and reduced Bacteroidetes. [139][140][141][142] Fecal microbial signatures of patients with cirrhosis vary with disease severity (compensated vs uncompensated cirrhosis) and might be used to predict outcomes of hospitalized patients. 143 Intriguingly, liver transplantation has been correlated with partial reversal of the gut dysbiosis associated with cirrhosis.…”
Section: Cirrhosis Spontaneous Bacterial Peritonitis Hepatic Encephmentioning
confidence: 99%
“…Microbiota dysbiosis was often reported in cirrhosis patients: (I) autochthonous/non-autochthonous taxa ratio reduction; (II) Firmicutes/Bacteroidetes ratio inversion; or (III) increased prevalence of potentially pathogenic bacteria [42,43,44]. Interestingly, the liver-gut axis was involved in the physiopathology of cirrhosis: overgrown intestinal bacteria have the potential to translocate across the leaky gut barrier and reach the liver, leading to cirrhosis development or progression [45]. However, few studies explored the gut microbiota in the context of S. japonicum infection-induced liver cirrhosis.…”
Section: Discussionmentioning
confidence: 99%